Pengaruh Kompetensi Pedagogik Guru Aqidah Akhlak terhadap Kualitas Proses Pembelajaran di Madrasah Tsanawiyah Negeri 2 Kebumen - Fitriani, Siami; Eliyanto, Eliyanto (IAINU Kebumen, 2025)
The purpose of this study was to determine whether there is an influence of the competence of aqidah akhlak teachers on the quality of the learning process in Madrasah Tsanawiyah Negeri 2 Kebumen. This research is a quantitative descriptive research. The respondents studied were 78 students of grade VIII Madrasah Tsanawiyah Negeri 2 Kebumen. The method used in this study is the questionnaire method. The data collected is in the form of questionnaire data regarding the influence of the competence of aqidah akhlak teachers on the quality of the learning process. The data analysis used is percentage quantitative analysis. The results showed that the pedagogical competence of aqidah akhlak teachers and the quality of the learning process in class VIII Madrasah Tsanawiyah Negeri 2 Kebumen were included in the good category. The pedagogical competence of aqidah akhlak teachers in the madrassa significantly influenced 57.9%, while the other 42.1% was influenced by other unexpected factors. So it can be concluded that the pedagogical competence of aqidah akhlak teachers has an influence on the quality of the learning process in Madrasah Tsanawiyah Negeri 2 KebumeThe purpose of this study was to determine whether there is an influence of the competence of aqidah akhlak teachers on the quality of the learning process in Madrasah Tsanawiyah Negeri 2 Kebumen. This research is a quantitative descriptive research. The respondents studied were 78 students of grade VIII Madrasah Tsanawiyah Negeri 2 Kebumen. The method used in this study is the questionnaire method. The data collected is in the form of questionnaire data regarding the influence of the competence of aqidah akhlak teachers on the quality of the learning process. The data analysis used is percentage quantitative analysis. The results showed that the pedagogical competence of aqidah akhlak teachers and the quality of the learning process in class VIII Madrasah Tsanawiyah Negeri 2 Kebumen were included in the good category. The pedagogical competence of aqidah akhlak teachers in the madrassa significantly influenced 57.9%, while the other 42.1% was influenced by other unexpected factors. So it can be concluded that the pedagogical competence of aqidah akhlak teachers has an influence on the quality of the learning process in Madrasah Tsanawiyah Negeri 2 Kebumen